Polyomavirus T Antigen Induces APOBEC3B Expression Using an LXCXE-Dependent and TP53-Independent Mechanism - Gabriel J. Starrett (American Society for Microbiology, 2019)
ABSTRACT APOBEC3B is a single-stranded DNA cytosine deaminase with beneficial innate antiviral functions. However, misregulated APOBEC3B can also be detrimental by inflicting APOBEC signature C-to-T and C-to-G mutations in genomic DNA of multiple cancer types. Polyomavirus and papillomavirus oncoproteins induce APOBEC3B overexpression, perhaps to their own benefit, but little is known about the cellular mechanisms hijacked by these viruses to do so. Here we investigate the molecular mechanism of APOBEC3B upregulation by the polyomavirus large T antigen. First, we demonstrate that the upregulated APOBEC3B enzyme is strongly nuclear and partially localized to virus replication centers. Second, truncated T antigen (truncT) is sufficient for APOBEC3B upregulation, and the RB-interacting motif (LXCXE), but not the p53-binding domain, is required. Third, genetic knockdown of RB1 alone or in combination with RBL1 and/or RBL2 is insufficient to suppress truncT-mediated induction of APOBEC3B. Fourth, CDK4/6 inhibition by palbociclib is also insufficient to suppress truncT-mediated induction of APOBEC3B. Last, global gene expression analyses in a wide range of human cancers show significant associations between expression of APOBEC3B and other genes known to be regulated by the RB/E2F axis. These experiments combine to implicate the RB/E2F axis in promoting APOBEC3B transcription, yet they also suggest that the polyomavirus RB-binding motif has at least one additional function in addition to RB inactivation for triggering APOBEC3B upregulation in virus-infected cells. IMPORTANCE The APOBEC3B DNA cytosine deaminase is overexpressed in many different cancers and correlates with elevated frequencies of C-to-T and C-to-G mutations in 5′-TC motifs, oncogene activation, acquired drug resistance, and poor clinical outcomes. The mechanisms responsible for APOBEC3B overexpression are not fully understood. Here, we show that the polyomavirus truncated T antigen (truncT) triggers APOBEC3B overexpression through its RB-interacting motif, LXCXE, which in turn likely modulates the binding of E2F family transcription factors to promote APOBEC3B expression. This work strengthens the mechanistic linkage between active cell cycling, APOBEC3B overexpression, and cancer mutagenesis. Although this mutational mechanism damages cellular genomes, viruses may leverage it to promote evolution, immune escape, and pathogenesis. The cellular portion of the mechanism may also be relevant to nonviral cancers, where genetic mechanisms often activate the RB/E2F axis and APOBEC3B mutagenesis contributes to tumor evolution.